Evidence - based pharmacological treatment of atopic dermatitis: An expert opinion and new expectations - Arnold P Oranje (Indian Journal of Dermatology, 2014)
Atopic dermatitis (AD) is one of the most common skin diseases with a complex multifactorial background. The clinical presentation, the aggravating factors and the complications vary according to the age of the patients. Most cases, approximately 60-80%, present for the 1 st time before the age of 12 months. Adult-onset AD has been observed as a special variant. Pruritus is the worst sign of AD, which also often indicates an exacerbation and is considered to be the most annoying symptom of AD. Treatment is preferably started based on the severity of AD. In only 10% of the cases, AD is so severe that systemic treatment is necessary. Systemic treatment including topical wet-wrap treatment is indicated in the worst and recalcitrant cases of AD. Systemic treatment of AD is discussed with regards to the evidence-based efficacy and safety aspects. I prefer wet-wraps as a crisis intervention in severe childhood cases, whereas UV and systemic treatments are the choices in patients older than 10 years. Probiotics are not useful in the treatment. If they have any effect at all it may only be in food-allergic children with AD. Finally, anti-histamines are not effective against pruritus in AD. They are only effective against urticarial flares and in cases with food-allergy. This article consists of an expert opinion on evidence-based pharmacological treatment of AD, but it is not a systemic review.